Determinants of firm value: evidence from listed insurance companies in Indonesia - I Ismiyatun; Nafiah Aryani; Heri Ispriyahadi (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2021)
This study was conducted to determine the effect of Return on Asset (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR) on firm value in insurance companies listed in Indonesia Stock Exchange from 2015 to 2019. The population in this research was 12 companies in various Insurance listed in the Indonesian Stock Exchange. The analytical method used three regression estimations (pooled OLS, fixed effects model (FEM), and random effects model (REM)). The results indicated that the Return on Asset, Debt to Equity Ratio, and Current Ratio had a significant negative effect on firm value. Our key finding from this research showed that when the profit was higher, the companies prefer to hold their earnings and use for an investment to generate growth opportunities. This phenomenon had explained when companies had higher yields, the firm's value went down. Therefore, this research is following the Pecking Order Theory. Further interaction analysis between DER and CR on firm value uncovers that both DER and CR also negatively affect firm value.